PENGARUH VISUAL MERCHANDISING, SHOPPING LIFESTYLE, DAN FASHION INVOLVEMENT TERHADAP PERILAKU IMPULSE BUYING: KONSUMEN HIGH INCOME - pebrianti, wenny; Yuwinda, Risa (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This research is conducted to find out the effect of visual merchandising, shopping lifestyle, and fashion involvement toward the impulse buying behavior to clothing storeâ€™s consumers â€œthis is aprilâ€ in Pontianak. The sampling used in this research is accidental sampling and the tool is multiple regression analysis. The result of data analysis shows that visual merchandising, and fashion involvement significantly affect the impulse buying, while shopping lifestyle does not significantly affect the impulse buying behavior. The ability of those three variables in explaning the effect toward the impulse buying 63,3% while the remaining 36,7% is expalined by the other factors outside the research models.